Who needs a superhero? New trends in action and adventure movies - Mancelos, João de (2016)
Is it a bird? Is it a plane? No, it’s (yet) another superhero who escapes from the drawing board to conquer de big screen. In recent years, movies like Iron Man 2 (2010), Thor (2010), Green Lantern (2011), Sucker Punch (2011) or The Dark Knight Rises (2012) have fascinated both comic and movie fans alike. Due to their popularity, a new wave of muscled and fierce heroes is coming, with X-Men: Days of the Future Past (2014), or The Fantastic Four (2015). The aim of this paper is to analyze the possible reasons behind the revival and acceptance of this genre, in order to explain this phenomenon. I argue that the answer is multifold and complex, resting in: a) Psychoanalysis (theory of the archetypes); b) Myth (the continuum theory); c) History (the 9/11 factor); d) Sociology (escapism and reassurance); e) Technology (the convenience of comic book adaptation and the possibilities operated by computer-generated imagery). In order to accomplish my mission, I resort to the studies of Carl Gustav Jung, Claude Lévi-Strauss, Joseph Campbell and other reputed specialists.